Second-life retailing: a reverse supply chain perspective - Beh, L.S.; Ghobadian, A.; He, Q.; Gallear, D.; O’Regan, N. (Emerald, 2016)
Purpose – The authors examine the role of entrepreneurial business models in the reverse supply chain of apparel/fashion retailers. The purpose of this paper is to offer an alternative approach to the “return to the point of origin” prevalent in the reverse chain of manufacturers but less technically and economically feasible in the case of apparel/fashion retailers. This approach, second-life retailing, not only reduces waste but also democratises consumption. Design/methodology/approach – The paper is based on an extensive literature review, semi-structured interviews with managers of two second-life retailers in Malaysia and observations of a number of stores. Findings – Using the Business Model Canvas, the authors demonstrate the essential characteristics of second-life retailers. Retailers in this study, unlike retailers in the developed world, combine traditional business models with off-price retailing. There is no clear demarcation between the forward and reverse supply chain used to manage first- and second-hand retailing. Practical implications – The paper demonstrates the potential of innovative business models in the reverse supply chain. It encourages managers to look beyond the “return to the point of origin” and seek imaginative alternatives. Such alternatives potentially could result in additional revenue, enhanced sustainability and democratisation of consumption meeting triple bottom line objectives. Originality/value – This paper highlights the importance and relevance of entrepreneurial business models in addressing the reverse supply chain, demonstrating this with the aid of two Malaysian off-price retailers. It also contributes to our nascent knowledge by focusing on emerging markets.